Three dimensional cutting force and tool deflection in micro-end milling AISI D2 / Noor Aniza Norrdin - Norrdin, Noor Aniza (2016)
The miniaturization of products demand has been increasing since it compromises advantages such as high and better portability, accessibility and functionality in medicals, automotive, aerospace, electronics, environmental and energy industries. In order to produce such a high demand product, an advanced manufacturing processes that can produce small parts, cost effectively and high productivity is required. Microend milling is one of the most promising manufacturing processes that capable in manufacturing parts with complex features in micro-scale (< 1000 um) due to its flexibility in processing a wide range of materials with a low setup cost. However, micro—end milling process has several challenges in precision manufacture of some products due to size effect. rapid tool wears, tool deflection and premature tool breakage. Moreover, the miniaturize products involve with tighter geometrical tolerance and high surface quality. These requirements and challenges make the selection of machining parameters for high performance micro—end milling more challenging. In this research, the development of a three- dimensional finite element model to simulate the micro-end milling operation of hardened AISI D2 cold work tool s‘eel based on the commercial finite element package Abaqus/Explicit. The Johnson-Cook material constitutive model was employed to model the flow stress behavior of the workpiece. Coulomb’s friction model was used to determine the frictional behavior of the tool-chip interface, Johnson—Cook damage model was used to realize chip separation and Arbitrary Lagrangian Eulen'an (ALE) formulation has been adopted for the workpiece to reduce distortions during simulations. Based on the three-dimensional finite element model, cutting forces in three directions, FL F, and F; were predicted under different cutting parameters (cutting speed, Vc, feed rate, f, depth of cut, :1) and cutting tool geometry (number of flutes; two, four, six, eight flutes and helix angle; 15° and 30°). Also. predictive models include outputs such as Von-Mimi stress, as well as performance related measures such as tool wears and tool deflection. It has been found that cutting force increases as the fwd rate, f and depth of cut, d increase and the cutting force decreases when high cutting speed, Vc were used. Also, the use high number of flutes and helix angle in cutting tool was expected to improve the performance of me and mills, especially in tenns of surface quality. Moreover, the larger cutting edge attained due to tool wear significantly increases the cutting forces, leading to (001 deflection. Therefore, thiis research demonstrates the capabilifies of micro-end milling in manufacturing micro-products of hardened AISI D2 mld work tool steel and an agreement of micro-milling force trends were achieved with the literature.